Phosphorus partitioning contribute to phosphorus use efficiency during grain filling in Zea mays - Sun, Yan; Han, Yang; Xu, Zikai; Zhang, Jinting; Shen, Jianbo; Cheng, Lingyun (Frontiers in Plant Science, 2023)
Introduction Lower phosphorus (P) availability limits crop productivity in agroecosystems. The remobilization of P from the source to the sink organs plays an important role in enhancing the P-utilization efficiency of crops. During the grain filling stage, phosphorus flow to the developing grains, the primary sink, determines crop yield. However, the specific contributions of different organs to grain P throughout the post-silking period in maize remain unclear. Methods In our study, three maize inbred lines (CIMBL89, Ji846, and CML118) with contrasting P statuses were selected and grown in a field with high P (HP, 150 kg ha–1 P2O5) and low P (LP, 0 kg ha–1 P2O5) conditions. Results The grain yield of CIMBL89 was 69% and 169% greater under HP supply, and 83% and 309% greater than those of Ji846 and CML118 under LP supply, respectively. The ear length, ear diameter, and kernel row number of CML118 were lower than those of CIMBL89 and Ji846 under HP conditions. Most of the P (87%) in the grains of CIMBL89 came from P uptake at the LP supply, while almost all P (95%) came from P remobilization in various organs at the HP supply after silking. In contrast, 91% of the P found in the grain of CML118 came from P remobilization under LP supply, while 76% came from P uptake under HP supply after silking. Discussion In conclusion, our findings suggest that CIMBL89, with greater P acquisition efficiency, contributes to grain formation and production during the post-silking period under LP conditions. Additionally, CIMBL89 can fully remobilize P and avoid the extravagant absorption of P in P-sufficient soil, which sets it apart from Ji846 and CML118.